Pseudomonas Aeruginosa Oligoribonuclease contributes to tolerance to ciprofloxacin by regulating pyocin biosynthesis - Chen, Fei (2018)
Bacterial oligoribonuclease (Orn) is a conserved 3′-to-5′ exonuclease. In Pseudomonas aeruginosa, it has been demonstrated that Orn plays a major role in the hydrolysis of pGpG, which is required for cyclic-di-GMP homeostasis. Meanwhile, Orn is involved in the degradation of nanoRNAs, which can alter global gene expression by serving as transcription initiation primers. Previously, we found that Orn is required for the type III secretion system and pathogenesis of P. aeruginosa, indicating a role of Orn in the bacterial response to environmental stimuli. Here we report that Orn is required for the tolerance of P. aeruginosa to ciprofloxacin. Transcriptome analysis of an orn mutant revealed the upregulation of pyocin biosynthesis genes. Mutation of genes involved in pyocin biosynthesis in the background of an orn mutant restored bacterial tolerance to ciprofloxacin. We further demonstrate that the upregulation of pyocin biosynthesis genes is due to RecA-mediated autoproteolysis of PrtR, which is the major negative regulator of pyocin biosynthesis genes. In addition, the SOS response genes were upregulated in the orn mutant, indicating a DNA damage stress. Therefore, our results revealed a novel role of Orn in bacterial tolerance to ciprofloxacin.